2017
DOI: 10.4012/dmj.2016-239
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of the susceptibility of cut and uncut enamel to erosive demineralization

Abstract: This study aimed to evaluate the susceptibility of cut and uncut enamel surfaces to an erosive challenge and to examine the resultant characteristics/morphological changes. Ten extracted human incisors were used for preparation of enamel samples, and samples were immersed in citric acid. After 3 (total 3 min) and 6 cycles (total 6 min) of erosive challenges, surface loss (SL) and morphological changes were measured using scanning microscopy and FIB-TEM. Ca release (CA) and surface hardness (SH) were measured u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
1
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 34 publications
2
10
1
1
Order By: Relevance
“…This suggests that acid erosion of human enamel has the effect of eliminating longer wavelength features which dominate the natural enamel surface [34], however it is not yet known to what extent this may be used to prevent progression of erosion. Natural enamel has been described as being more resistant to erosion compared to polished enamel and certainly the effects of erosion are less pronounced [12,13,15,16,33]. This study supports this previous work and has identified that natural or polished enamel surfaces exhibit contrasting responses to a similar erosive challenges, thus suggesting that preserving the acidresistant outer layer of enamel may be essential for clinical management for erosive wear [35].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This suggests that acid erosion of human enamel has the effect of eliminating longer wavelength features which dominate the natural enamel surface [34], however it is not yet known to what extent this may be used to prevent progression of erosion. Natural enamel has been described as being more resistant to erosion compared to polished enamel and certainly the effects of erosion are less pronounced [12,13,15,16,33]. This study supports this previous work and has identified that natural or polished enamel surfaces exhibit contrasting responses to a similar erosive challenges, thus suggesting that preserving the acidresistant outer layer of enamel may be essential for clinical management for erosive wear [35].…”
Section: Discussionsupporting
confidence: 85%
“…In vitro erosive tooth wear models normally employ polishing of enamel to remove the outer layer to reduce structural variations, and thus facilitate measurement [11]. However, this means the outer layer, which contains areas of aprismatic and prismatic enamel which is less susceptible to erosion [12][13][14][15][16], has been removed and therefore the erosion model maybe less clinically relevant.…”
Section: Introductionmentioning
confidence: 99%
“…A limitation of the present study is that the enamel samples were ground and polished for SMH measurements. Thus, the current findings should be interpreted with caution since the native enamel provides innate resistance to erosive attacks [39]. Additionally, although CPP-ACP is claimed to be the only active agent of Tooth Mousse tested, the protective effects against erosion may not be solely related to CPP-ACP since the distilled water was used as a control.…”
Section: Discussionmentioning
confidence: 80%
“…For these kinds of studies mainly polished enamel specimens were applied out of methodological reasons, irrespective of the fact if they were of bovine or human origin. It was shown, however, that erosive attacks affect native and polished enamel surfaces differently (Meurman & Frank, 1991;Ganss, Klimek, & Schwarz, 2000;Lin, Kitasako, Nakashima, & Tagami, 2017;Mullan, Bartlett, & Austin, 2017;Mullan, Austin, Parkinson, & Bartlett, 2018). Superficial enamel layers differ from underlying regions in terms of degree of mineralization, water content and level of trace elements like fluoride (Sullivan, 1954;Hallsworth & Weatherell, 1969).…”
Section: Main Text Introductionmentioning
confidence: 99%